Analysis of do-not-spam registry - Eran Reshef; Eilon Solan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2005)
We study how the launching of a do-not-spam registry will affect the internet's efficiency. We show that as long as the cost of sending spam messages is not high, having rich users (who have high-quality filters) join the registry has the desirable effect of lowering the number of spam messages sent to each user, while having poor users (who have low-quality filters) join the registry has the opposite undesirable effect. We also show that the registry improves the total efficiency of the internet - as long as the cost of sending spam messages is not high; as more users join, the total number of spam messages sent to all users decreases.
Keywords: 330; Online-Werbung; Internet; Wirtschaftliche Effizienz; Theorie